A Standard Test Apparatus and Method for Validating the Accuracy of Mobile Phone Apps in Measuring Concrete Crack Widths - Chyuan-Hwan Jeng; Min Chao; Jian-Hung Chen (Eng)
This paper presents a standardized apparatus and method for testing the accuracy of mobile phone apps designed to measure concrete crack widths. The apparatus comprises a standardized crack-width calibration plate (CWCP) and a simulated wall (SW), along with a pose adjusting and fixing device (PAFD) and a spatial distance measuring assemblage (SDMA). The test method employs an innovative two-stage procedure associated with the SDMA to calculate the distances (Ki) from the phone’s four corners to the SW. The phone’s position is adjusted using the PAFD until the four monitored Ki values match the target Ki. An app installed on the phone then measures crack widths on the CWCP. A standard experimental procedure was established to assess the accuracy of a preliminary Android app in measuring concrete crack widths, with results presented and discussed. This apparatus and method, grounded in their underlying physical meaning, can realistically simulate actual engineering conditions precisely and cost-effectively.